Pharmacokinetics of once-daily theophylline dose following the morning versus evening administration - Trnavská, Z; Vondra, V; Elis, J (Arzneimittel-Forschung, 1989)
The pharmacokinetics of theophylline (Uniphyllin) in blood and saliva was compared after morning and evening administration of a once-daily dose in a randomized cross-over study. Ten bronchial asthma patients received multiple doses of 800 mg theophylline at 8 a.m. and 8 p.m. under controlled food conditions. The precision of the serum concentration prediction from salivary measurements in individual patients was sufficient to obtain identical pharmacokinetic parameters and parallel concentration-time curves. There were no significant differences in the values of mean residence time and area under the concentration-time curves after morning and evening dosing, either in the kinetics of elimination and in the volume of distribution. The fluctuation of concentrations during the dosing intervals was 100% after morning doses and 80% after evening doses. No consistent interference with food was found. Circadian variation in the kinetics of drug disposition after once-daily theophylline administration did not occur. In order to achieve higher therapeutical levels at night and in the morning, the evening dosing seems to be preferable.
Keywords: rozvrh dávkování léků; náhodné rozdělení; mužské pohlaví; Drug Administration Schedule; Male; theofylin; Humans; Female; lidé; Middle Aged; ženské pohlaví; lidé středního věku; Theophylline; Half-Life; Random Allocation; dospělí; Adult; Saliva; poločas; sliny